2006
DOI: 10.1103/physrevlett.97.194101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Induced Resonance

Abstract: We present conclusive evidence showing that different sources of diversity, such as those represented by quenched disorder or noise, can induce a resonant collective behavior in an ensemble of coupled bistable or excitable systems. Our analytical and numerical results show that when such systems are subjected to an external subthreshold signal, their response is optimized for an intermediate value of the diversity. These findings show that intrinsic diversity might have a constructive role and suggest that nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
192
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(205 citation statements)
references
References 13 publications
(16 reference statements)
10
192
1
1
Order By: Relevance
“…The most intriguing part of the phenomenon is that noise (a source of disorder) can favor the amplification of a signal, an effect that usually requires a very precise synchrony (order). Recently in [11], it has been shown that even in absence of noise a similar beneficial effects can be observed. There, different sources of diversity plays the role of the noise, inducing a resonant collective behavior.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The most intriguing part of the phenomenon is that noise (a source of disorder) can favor the amplification of a signal, an effect that usually requires a very precise synchrony (order). Recently in [11], it has been shown that even in absence of noise a similar beneficial effects can be observed. There, different sources of diversity plays the role of the noise, inducing a resonant collective behavior.…”
mentioning
confidence: 86%
“…The two possible solutions for the nodes Eq. (5), namely oscillations around ±1, affect the dynamics of the hub as a quenched disorder represented by λη i , and is equivalent to the diversity studied in [11]. Strictly speaking, the central limit theorem allows us to state that in the limit N → ∞, η i behaves as a random variable governed by a gaussian probability distribution with variance σ 2 = N − 1.…”
mentioning
confidence: 99%
“…Such diversity can be expected to lead to more robust operation of the system under variation of external conditions, due to the averaging of the neuronal responses. Diversity has also been proposed as a sourceofregular behavior in nonlinear systems (Tessone et al, 2006).…”
Section: Figurementioning
confidence: 99%
“…It has been recently shown that diversity might play an important role in forced excitatory systems, equivalent to the one played by noise in the stochastic resonance phenomena (Tessone et al 2006). Tessone et al (2006) demonstrated that the response of a system to an external weak periodic signal can be optimized by an intermediate level of diversity between the elements composing the system even in the absence of any other noise source. Consequently, diversity (represented by a quenched noise) and stochastic noise seem to play qualitatively the same role.…”
Section: Mathematical Formulas and Model Parameters Used In Computer mentioning
confidence: 99%